2022
DOI: 10.1155/2022/7827821
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statin Use with the Risk of Incident Prostate Cancer: A Meta-Analysis and Systematic Review

Abstract: Background. With the growth and aging of population, the incidence of prostate cancer will increase year by year, which is bound to bring greater economic burden to the society. There has been greater interest in the anticancer effects of statin in recent years. It is controversial whether statin use is associated with the risk of prostate cancer (PCa). Thus, we conducted a meta-analysis and systematic review to explore the effects of statin use and their duration and cumulative dose on the overall incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…[ 42 ] Statins have anti-inflammatory, immunomodulatory effects, and can also induce prostate cancer cell death by promoting autophagy pathways. [ 43 ] Several meta-analyses also support our view, [ 44 , 45 ] and we further found that BT could potentially lower PCa. BT is a part of testosterone that is easily diffused, so it can better reflect the biological activity of testosterone than TT.…”
Section: Discussionsupporting
confidence: 86%
“…[ 42 ] Statins have anti-inflammatory, immunomodulatory effects, and can also induce prostate cancer cell death by promoting autophagy pathways. [ 43 ] Several meta-analyses also support our view, [ 44 , 45 ] and we further found that BT could potentially lower PCa. BT is a part of testosterone that is easily diffused, so it can better reflect the biological activity of testosterone than TT.…”
Section: Discussionsupporting
confidence: 86%
“…The pooled results of 6 randomized control trials (RCTs) and 26 cohort studies indicated a non-significant relationship between statins and prostate cancer occurrence (RR = 0.94, 95% CI: 0.82 to 1.08). Similar results were also achieved from nine case-control studies (OR = 1.03, 95% CI: 0.99 to 1.07) (34). Our results corroborate those of the above meta-analysis, suggesting their findings, statin administration did not affect the OS of RCC patients compared to the control groups (OR = 1.07, 95% CI: 0.77, 1.49, P = 0.68) (35), which contradicts the results of the present meta-analysis.…”
Section: Discussionsupporting
confidence: 82%
“…ADT encompasses various treatment modalities aimed at lowering the levels of circulating androgens and blocking their effects on prostate cancer cells [ 22 ]. A recent meta-analysis comprising 41 studies did not find a significant association between statin use and the incidence of prostate cancer [ 23 ]. However, among patients who underwent primary therapies such as RP and/or RT, the use of statins was linked to a 22% reduction in the risk of metastasis and a 24% reduction in the risk of mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%